Care in the community : recent research and current projects ; papers arising from two seminars - Glendenning, Frank; University of Keele. Department of Adult Education; Beth Johnson Foundation (Stoke-on-Trent : Beth Johnson Foundation ; in association with the Dept. of Adult Education, University of Keele and Age Concern England, 1982)
Een stand van zaken wat betreft de publieke zorgverlening.